The Portrayal of the German in Russian Novels - Gončarov, Turgenev, Dostoevskij, Tolstoj - Schulz, Robert Kenneth (Slavistische Beitraege, 1969)
It is the intention of this dissertation to investigate, as thoroughly as possible, the portrayal of the German as he appears in the prose works (drama and poetry have been excluded) of four of Russia's greatest nineteenth-century literary writers- I. A, Gončarov, I. S. Turgenev, F. M. Dostoevskij, and L. N. Tolstoj.